Fatores de risco para mortalidade de recém nascidos com asfixia perinatal em uma maternidade de risco habitual - Resende, Luana Teles de (2021)
Introduction: perinatal asphyxia is one of the main causes of infant mortality in the world, characterized by oxygen deprivation in prenatal, delivery or after birth, which compromises the organic functions of newborns, especially the central nervous system. Thus, understanding the risk factors associated with mortality can guide the planning of public policies aimed at maternal and child health. Objective: to evaluate the risk factors related to mortality in newborns with perinatal asphyxia in a usual risk maternity hospital. Methodology: observational cross-sectional study with a quantitative approach carried out in a usual risk maternity hospital in Aracaju / SE. The research population consists of newborns with perinatal asphyxia admitted to the Neonatal Intensive Care Unit (NICU), between January to July 2019, and followed up until their final outcome (discharge or death). The data were obtained through interviews with the mother and information contained in the Declaration of Live Birth, in addition to the medical records of the mothers and newborns. The observed variables were grouped into sociodemographic data, maternal history, obstetric data and neonatal information. For quantitative variables, the Mann-Whitney test was applied and, for categorical variables, the Chi-square test and Fisher's exact test. Mortality rate and Odds Ratio (OR) were calculated to assess the risk of death. The research was approved by the Ethics and Research Committee of the Federal University of Sergipe, under opinion number 3,013,700 and met the recommendations of resolution number 466/2012 of the National Health Council. Results: the mortality rate obtained was 3.65 deaths / thousand live births. The risk factors for mortality from perinatal asphyxia were: low Apgar score at the 5th minute (OR 5.2; p = 0.009), hypothermia at birth (OR 3.1; p = 0.029), use of mechanical ventilation in the NICU (OR 3.7; p = 0.047) and the presence of anemia (OR 3.7; p = 0.013). Maternal and obstetric factors were not statistically significant with the death of newborns with perinatal asphyxia. Conclusion: neonatal risk factors reflect a higher mortality of babies with perinatal asphyxia. Therefore, quality care in the prenatal and delivery period can prevent such occurrences, just as care after birth can minimize complications and reduce the mortality of newborns with asphyxia.